Registros gráficos do alçamento vocálico em produções escritas de alunos em processo de alfabetização - Souza, Viviani Dias Barradas de (2023)
This Master thesis of the subject of the graphic recording of vowel raising processes in the written productions of students in the literacy process. The general aim is to develop a didactic unit with activities focused on the phenomenon of vowel raising processes, according to graphic records of the phonological process and written productions by students in the literacy process. The research is justified because it deals with a speech phenomenon that is present in Brazilian Portuguese and which is transcribed into writing. In this case, classroom work requires reflection on orality, in order to make students understand that writing follows arbitrary rules that are opaque in relation to speech. We chose this phenomenon to contribute to teaching practice through reflections that problematize graphic notation, in an attempt to prevent students from generalizing rules and starting to spell as in the following examples: buneca, for doll, and tomati, for tomato. The vowel raising processes was chosen as the subject of this research due to the frequent number of graphic registers in students' written activities. We wait that this research can contribute to the work of elementary school Portuguese language teachers. This Master thesis was developed by means of interpretative qualitative research, with the expectation of aiding knowledge about the aforementioned phonological process, committed to uniting theory and practice and promoting knowledge.The theoretical framework is based on studies by authors who draw on studies on literacy and literacy in the oral and written modality of the Portuguese language, phonological aspects and phonological processes, as well as the appropriation of writing, such as Mattoso Câmara Jr (1976, 1999, 2008), Cagliari (2000, 2002), Silva (2005), Zorzi (2006), Bisol (2009), Lemle (2009), Marcuschi (2005), Faraco (2005), Fayol (2014), Ferreira and Busse (2019), Soares (2005, 2017, 2021), Bortoni-Ricardo (2004), Abaurre (2011), among other researchers. In choosing this process for this Master thesis, we sought to present activities that help students reflect on vowel raising processes, so that they don't start to generalize the rule and incur hypercorrections. We therefore stress the importance of the teacher leading the students to reflect on their writing in a systematized way, so that they can build a more reflective attitude towards speech and writing, still during literacy.